The role of gene polymorphism of some immune response molecules in the development of acute virus-induced bronchiolitis - L. S. Bochkareva; N. A. Miromanova; A. M. Miromanov (Журнал инфектологии, 2022)
The aim of research: To investigate the genetic polymorphism of immune response molecules (TNFα-308G> A (rs1800629), IL4-589C>T (rs2243250), IL10-592C> A (rs1800872), IL10-819C> T (rs1800871), IL10-1082G>A (rs1800896), IL-17A-197G> A (rs2275913), IL- 17F-161His> Arg (rs763780), TLR-2-753Arg>Gln (rs5743708), TLR-6-249Ser>Pro (rs5743810) and assess their prognostic value in the development of acute virus-induced bronchiolitis.Materials and methods. The study included children of the first year of life, whose average age was 4.2 ± 3.7 months. The main group consisted of 106 patients with moderate and severe acute viral bronchiolitis, more often associated with respiratory syncytial virus (56.6%). The control group consisted of 100 healthy children of the same age who had no signs of acute respiratory infection at the time of examination and did not receive passive immunoprophylaxis of respiratory syncytial infection. Genotyping was performed using the polymerase chain reaction method. The analysis of the results included the compliance with the Hardy-Weinberg law, the χ 2 test, the relative chance, and its 95% confidence interval. To assess the distribution of the claimed gene polymorphisms and their alleles, we used the general (χ2 test, df =2) and multiplicative (χ2 test, df =1) inheritance models.Results. It was revealed that the risk of developing acute viral bronchiolitis is increased compared to the healthy population in carriers of the following genotypes: CC, ST gene IL10-819C> T (rs1800871), GG, AA gene IL-17A-197G> A (rs2275913), HisHis gene IL-17F-161His> Arg (rs763780), SerSer, SerPro gene TLR-6-249Ser> Pro (rs5743810), GG gene TNF-α-308G>A (rs1800629). The TT genotype of the IL10-819C>T (rs1800871) gene is associated with a high risk of developing bacterial complications (pneumonia) in viral bronchiolitis. Carriers of genotypes AA, CC of the IL10-592C> A (rs1800872) gene have an increased likelihood of a severe course of viral bronchiolitis.Conclusion. Genetic analysis of gene polymorphism IL10-592C> A (rs1800872), IL10-819C> T (rs1800871), IL-17A-197G> A (rs2275913), IL-17F-161His> Arg (rs763780), TLR-6-249Ser> Pro (rs5743810), TNF-α-308 G>A (rs1800629) can be used as a personalized developmental criterion acute virus-induced bronchiolitis in children, determining the severity of its course and the likelihood of complications.